The Mediating Role of Work Motivation in the Relationship Between Organizational Culture, Job Training, and Employee Performance - Yusnina Yusnina; Ari Prihatni; Ririn Widyastuti Wulaningsih; Lisdawati Lisdawati; Erita Oktasari (International Journal of Marketing & Human Resource Research, 2026)
The Indonesian coffee industry has developed rapidly and has become an integral part of modern lifestyle consumption. Starbucks Indonesia, as a market leader, relies heavily on effective human resource management to maintain service quality and competitive advantage. However, Starbucks Grand Indonesia Mall faces several challenges related to organizational culture, the effectiveness of job training, and employee motivation, particularly among employees aged 18–24 years. This study examines the effects of organizational culture and job training on employees’ work motivation and, in turn, their performance at Starbucks Grand Indonesia Mall. A quantitative research design was adopted, applying both descriptive and explanatory approaches. The study involved 49 employees, all of whom participated as respondents via a census (saturated sampling) method. Data were gathered using structured questionnaires measured on a Likert scale, supported by observations and interviews. Path analysis was utilized to evaluate the direct and indirect relationships among the research variables. The findings demonstrate that both organizational culture and job training exert a positive and statistically significant influence on employees’ work motivation, accounting for 54% of the observed variance. In addition, organizational culture, job training, and work motivation, both collectively and individually, have significant effects on employee performance, accounting for 67% of the total variation in performance outcomes. Among these predictors, job training emerges as the most influential determinant of employee performance. This study extends the existing human resource management literature by providing empirical evidence from Indonesia’s retail coffee service industry, with particular attention to the mediating role of work motivation. By empirically validating this relationship, the study provides a deeper understanding of how organizational practices translate into performance outcomes. The findings offer strategic implications for practitioners, particularly in designing integrated human resource frameworks that foster sustainable employee performance and strengthen long-term organizational competitiveness.